THE EFFECT OF CONVERGENCE OF REGIONAL ORIGINAL INCOME AND BALANCING FUNDS ON FINANCIAL PERFORMANCE WITH HUMAN DEVELOPMENT INDEX AS A MODERATION VARIABLE IN REGENCY/CITY GOVERNMENTS IN NORTH SUMATRA - Fahrum Nisa; Agus Tripriyono (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the effect of the convergence of Local Own-Source Revenue (PAD) and Transfer Funds on regional financial performance with the Human Development Index (HDI) as a moderating variable. The data used in this research include the realization of PAD, Transfer Funds, Regional Expenditures, and HDI in ten selected regencies/cities in North Sumatra Province (Medan, Binjai, Padangsidimpuan, Deli Serdang, Asahan, Toba, North Tapanuli, Mandailing Natal, Gunungsitoli, and South Nias) during the period 2020–2024.The analytical method employed is panel data regression using EViews, consisting of model selection tests (Chow, Hausman, and Lagrange Multiplier tests), classical assumption tests, and estimation using the Fixed Effect Model (FEM).The results show that PAD has a positive and significant effect on regional financial performance. In contrast, Transfer Funds and HDI have no significant effect. Moreover, HDI is not proven to moderate the relationship between PAD or Transfer Funds and regional financial performance. These findings emphasize that fiscal independence through PAD is the main factor in improving regional financial performance, while the roles of Transfer Funds and HDI remain limited, especially during the COVID-19 pandemic.